Diagnóstico del impacto socio ambiental de los utensilios plásticos descartables utilizados para la venta ambulante de comidas preparadas en la zona céntrica de la ciudad de Pasaje, provincia de El Oro periodo 2013-2015 - Calle Pineda, Byron de Jesús (2014)
This research, contains reliable information regarding the socio-environmental reality and health in the sale of prepared foods that are sold as a street vendor and they are consumed by a large number of the population of the city of Passage is done. The diagnosis shows that food purchased diners mostly is done in disposable plastic utensils that are exposed to high temperatures and as suggested by Edward Fujimoto they release dioxins that are introduced into the food and ultimately into the cells of our body as well when meals are covered with plastic wrap and very hot, plastic-laden drips poisonous toxins on the food.